Kepercayaan, Kepuasan dan Pengorbanan Pelanggan Terhadap Chatbot: Layanan Pelanggan Berbasis Artificial Intelligence pada E-commerce Shopee - Rizqy, Rahmatin Sabila; Hartono, Arif (Jurnal Ecogen, 2025)
The development of artificial intelligence (AI) technology has driven the creation of AI-based customer service on e-commerce. Several researchers have tried to reveal customer experience triggers using AI-based customer service, but there are still inconsistencies in the research results. Therefore, this study aims to examine the triggering factors for AI-based customer experience in e-commerce and to test customer trust, satisfaction, and sacrifice as mediator variables of this relationship. The research method used convenience sampling and obtained 251 research samples from chatbot users on the Shopee e-commerce through an online survey and analyzed using SPSS and PLS-SEM with the SmartPLS device. The results of this study indicate that service quality, trust, and customer satisfaction have a positive and significant effect on AI-based customer experience. There was no positive and significant relationship between perceived sacrifice and customer experience. In addition, customer trust and satisfaction can mediate the relationship between AI-based service quality and e-commerce customer experience. This study enriches the marketing literature and provides recommendations to marketing managers to manage customer experience triggers in the context of AI-based customer service in e-commerce.